2018
DOI: 10.3389/fphys.2018.00901
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Hypoxia-Induced Vascular Dysfunction in Rats is Reverted by N-Acetylcysteine Supplementation and Arginase Inhibition

Abstract: Chronic intermittent hypoxia (CIH), the main attribute of obstructive sleep apnea (OSA), produces oxidative stress, endothelial dysfunction, and hypertension. Nitric oxide (NO) plays a critical role in controlling the vasomotor tone. The NO level depends on the L-arginine level, which can be reduced by arginase enzymatic activity, and its reaction with the superoxide radical to produce peroxynitrite. Accordingly, we hypothesized whether a combination of an arginase inhibitor and an antioxidant may restore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
(91 reference statements)
0
22
0
Order By: Relevance
“…Furthermore, NAC has been proven to restrain renin expression in the renal tissue [45]. Finally, according to Krause et al [46], NAC by its antioxidant activity and glutathione supply could improve hypertension in cases of increased OS associated with elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NAC has been proven to restrain renin expression in the renal tissue [45]. Finally, according to Krause et al [46], NAC by its antioxidant activity and glutathione supply could improve hypertension in cases of increased OS associated with elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“… 12 14 We have previously demonstrated that the CIH pattern used in this study produces systemic oxidative stress 31 and endothelial dysfunction. 32 , 33 High levels of ROS raise [Ca 2+ i], in PASMC, which is the key factor in differentiation and proliferation of vascular smooth muscle. 42 , 43 In PASMC, [Ca2+i] may increase by the activation of two mechanisms: (1) release of Ca2+ from the sarcoplasmic reticulum, mediated by intracellular channels sensitive to inositol trisphosphate (IP3) or by ryanodine receptors (RyR), or (2) by the entry of Ca2+ from the extracellular space mediated by the Na+/Ca2 exchanger, Ca2+ type L channels, and stretch-activated Ca2+ channels.…”
Section: Discussionmentioning
confidence: 99%
“…Unrestrained, freely moving rats were housed in individual chambers and exposed to hypoxic cycles of 5% inspired O 2 for 20 s, followed by 280 s of room air, 12 times per hour for 8 h a day for 14, 21, and 28 days. 31 33 Rats were exposed to CIH from 8:00 a.m. to 4:00 p.m. The O 2 level inside the chambers was continuously monitored with an oxygen analyzer (Ohmeda 5120, BOC Healthcare, Manchester, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A computerized system controlled the valve inlets and the alternating cycles of the extractors. The CO 2 in the chamber was maintained at a low level by continuous air extraction (14). Rats in the control group were maintained under normoxic conditions during the experiment.…”
Section: Methodsmentioning
confidence: 99%